Quantifying abundance and distribution of native and invasive oysters in an urbanised estuary - Scanes, E; Johnston, E L; Cole, V J; O’Connor, W A; Parker, L M; Ross, P M (Aquatic Invasions, 2016)
Human activities have modified the chemical, physical and biological attributes of many of the world’s estuaries. Natural foreshores have been replaced by artificial habitats and non-indigenous species have been introduced by shipping, aquaculture, and as ornamental pets. In south east Australia, the native Sydney rock oyster Saccostrea glomerata is threatened by pollution, disease and competition from the invasive Pacific oyster Crassostrea gigas. This study assessed the abundance (as number m-2), size, and distribution of both invasive and native oyster species at 32 sites in the heavily urbanised Port Jackson Estuary, Australia. We tested the hypotheses that there would be: (1) a difference in the proportion of C. gigas and S. glomerata among locations; (2) a greater proportion of C. gigas on artificial compared to natural substrates; (3) a greater numbers of all oysters, with differing size characteristics, on artificial compared to natural substrates; and (4) that the abundance and size of all oysters would vary among locations along an environmental gradient. Environmental variables included distance from the estuary mouth and salinity. We found the abundance and size of all oysters differed among locations; smaller oysters occurred at greater abundances near the mouth of the estuary. Abundance was also higher on artificial, than on natural substrate. Habitat type, however, had no effect on which species of oyster was present. In contrast, distance from the estuary mouth strongly influenced the relative proportion of the two species. The invasive C. gigas comprised 16% of the oysters sampled, and up to 85% at some of the upper estuary sites. As predicted, C. gigas was more abundant at locations in the bay ends and upper channel of the estuary; it was also larger in size than the native S. glomerata. This is the first assessment of oyster distribution in Port Jackson and provides a solid base for monitoring changes in the estuarine distribution of a globally invasive pest. © 2016 The Author(s). Journal compilation, 2016 REABIC.